Hannibal Lokumbe spiritual soundscapes of music, life, and liberation - Coyle Rosen, Lauren 1983-; Lokumbe, Hannibal 1948- (Columbia University Press, 2024)
"For the musician Hannibal Lokumbe, sound is not solely tonal or aural. It also has feeling, textures, scents, colors, contours, and other spatial, material, and sensorial dimensions. These multi-sensorial spiritual soundscapes are sonic spaces that allow for a reckoning with previous traumas or suffering - such as the Birmingham Church Bombing, the Vietnam War, or the Middle Passage into slavery - which may lead to healing or illumination in the present or future. His musical compositions - whether jazz, orchestral, oratorios, string quartets, or other genres - are centered on addressing the African American experience through spiritual soundscapes that chronicle as well as heal and liberate. His work pays special tribute to the experiences of Africans and Native Americans. One of his primary spirit guides is his maternal great-grandmother, Cora, a Cherokee shaman who successfully fled the Trail of Tears. She, along with Hannibal's mother who is now in spirit, plays a key role in guiding and inspiring his major works and life decisions. The ancestors and other trusted spirits inform him at every turn as he proceeds, through dreams, visions, and other modalities of transmission and affective relation. Hannibal Lokumbe by Lauren Coyle Rosen is an experimental ethnographic profile of the lifelong journey of musical creativity, liberation work, and spiritual practices of Hannibal Lokumbe, a pathbreaking orchestral composer, librettist, poet, and jazz musician. Building upon and combining recent anthropological and musical work on soundscapes, affective archives, spiritual co-presences, and liberation art, through the life of Lokumbe Coyle Rosen demonstrates the centrality of a concept called spiritual soundscapes, which emerged throughout her extensive conversations with him over recent years. She explains how Lokumbe perceives music to be a spiritual healing force and a living consciousness that can liberate."
Keywords: Lokumbe, Hannibal -- 1948-; Lokumbe, Hannibal / 1948-; Lokumbe, Hannibal / 1948- / Religion; Composers / United States / Biography; African American composers / Biography; Trumpet players / United States / Biography; Jazz musicians / United States / Biography; African American jazz musicians / Biography; Biografie